2002
DOI: 10.1093/jn/132.6.1115
|View full text |Cite
|
Sign up to set email alerts
|

Trans-10,cis-12 Conjugated Linoleic Acid Suppresses the Desaturation of Linoleic and α-Linolenic Acids in HepG2 Cells

Abstract: The objective of this study was to determine the effects of cis-9,trans-11 and trans-10,cis-12 CLA on the fatty acid desaturation in a human hepatoma cell line, HepG2. Therefore, experiments were conducted in which HepG2 cells were incubated with various concentrations of those fatty acids and the concentrations of fatty acids in various lipid fractions of HepG2 cells were determined. In the presence of linoleic acid as substrate, cells treated with 25 micromol/L of trans-10,cis-12 CLA had lower ratios of diho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 22 publications
5
48
2
Order By: Relevance
“…In mammals, CLA is also known to decrease the activity and gene expression of SCD and may also suppress Δ6 and Δ5 desaturases, and elongase (Choi et al, 2001(Choi et al, , 2002Chuang et al, 2001a,b;Eder et al, 2002 have some similar effects in salmon. Thus, there was an indication that SCD in liver was reduced as evidenced by increased 18:0 and decreased 18:1n-9, and a similar effect was observed previously in salmon fry fed CLA (Berge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, CLA is also known to decrease the activity and gene expression of SCD and may also suppress Δ6 and Δ5 desaturases, and elongase (Choi et al, 2001(Choi et al, , 2002Chuang et al, 2001a,b;Eder et al, 2002 have some similar effects in salmon. Thus, there was an indication that SCD in liver was reduced as evidenced by increased 18:0 and decreased 18:1n-9, and a similar effect was observed previously in salmon fry fed CLA (Berge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased body fat has also been observed in human studies (Smedman and Vessby, 2001;Thom et al, 2001;Riserus et al, 2001) although the effect was much less than that observed with mice (Terpstra, 2004). CLA is also known to decrease the activity and gene expression of mammalian stearoyl CoA Δ9 desaturase (SCD) (Choi et al, 2001(Choi et al, , 2002 and may also suppress Δ6 and Δ5 desaturase (Chuang et al, 2001a;Eder et al, 2002) and elongase (Chuang et al, 2001b). Further studies have suggested that CLA may enhance growth and feed efficiency in young rodents ) although this has not been consistently observed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the trans-10,cis-12 isomer of CLA has been shown to inhibit fatty acid desaturation by decreasing the activity or mRNA levels of Δ9-, Δ6-, and Δ5-desaturases in murine preadipocytes or hepatic microsomes, human breast cancer cells, and human hepatocytes (21)(22)(23)(24)(25). This trans-10,cis-12 CLA-mediated reduction in fatty acid desaturation results in a decreased monounsaturated fatty acid (MUFA) to saturated fatty acid (SFA) ratio (21,23). It has been postulated that without adequate levels of the MUFA oleate, a preferential substrate for TG synthesis (26), TG levels are diminished.…”
mentioning
confidence: 99%
“…Thus, the dose of individual isomers may be relatively low despite high intakes of total CLA compared with the basal diet. Because some effects of CLA may be isomerspecific (11,12,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), differences in the intake of bioAbbreviations: CE, cholesteryl ester; CLA, conjugated linoleic acid; FAME, fatty acid methyl ester; NEFA, nonesterified fatty acid; PBMC, peripheral blood mononuclear cell; PC, phosphatidylcholine. …”
mentioning
confidence: 99%